Status and diversity of arbuscular mycorrhizal fungi and its role in natural regeneration on limestone mined spoils - ANUJ KUMAR SINGH; JAMALUDDIN JAMALUDDIN (Biodiversitas Journal of Biological Diversity, 2011)
Singh AK, Jamaluddin (2011) Status and diversity of arbuscular mycorrhizal fungi and its role in natural regeneration on limestone mined spoils. Biodiversitas 12: 107-111. Limestone mined spoils are devoid of adequate population of beneficial microbial flora. Arbuscular mycorrhizal fungi (AMF) are very important constituent of plant- soil-microbe system. In mined spoils the population of AMF is greatly reduced and hence the spoils become very inhospitable for establishment of vegetation. In the present investigation, status of AMF population and its effect on natural regeneration process is studied. It is well known fact that the arbuscular mycorrhizalfungi play very important role in establishment of vegetation in degraded lands. Plantation of seedlings inoculated with arbuscular mycorrhizal fungi provide favorable soil conditions for naturally growing vegetation in the mined overburden spoils. Physico-chemical properties of soil are converted suitable for planted species and thus it allows other species to grow and also provide shade to protect the herbaceous vegetation. Introduction of plant species attracts immigration of other species and if they established, may result into a very distinctive floral cover on disturbed lands. Thus, invasion of native plant species along with planted species may play a significant role in increasing the plant diversity on mined spoils.